Catalase activity in Smicridea McLachlan, 1871 (Insecta, Trichoptera) collected from natural and altered/impacted streams - Biasus,Cristiane (2015)
Aim: We compare catalase activity in SmicrideaMcLachlan, 1871 (Insecta, Trichoptera) collected in natural and agricultural streams and correlates the enzyme pattern with metal content in the water.MethodsOrganisms were collected in sites classified as natural (riparian vegetation in buffer zone) and altered/impacted (agricultural land use in drainage area) environments, located at Cravo River and Campo River sub-basins (RS, Brazil). Next the collected larvae were identified and used to proteins quantification and catalase activity measure. The concentration of Mg, Cr, Cu, Pb and Cd in the water was determined by atomic absorption spectrometry.ResultsCatalase activity in Smicridea ranged from 1.5 to 6 U, with mean values about 2.63 ± 0.096 U (SEM). The presence of metals was higher in the streams located at agricultural drainage area, except for Mg at the Cravo sub-basin and Cu at the Campo sub-basin. Catalase was higher in Smicridea collected in natural streams as compared to that agriculture streams and was correlated with Pb and Cd levels.ConclusionsThe data showed the potential of this biomarker as a useful tool for complementation of water quality biomonitoring studies using Smicridea as bioindicator.